Volumetric assessment of glioblastoma and its predictive value for survival - Henker, Christian; Hiepel, Marie Cristin; Kriesen, Thomas; Scherer, Moritz; Glass, Änne; Herold-Mende, Christel; Bendszus, Martin; Langner, Sönke; Weber, Marc-André; Schneider, Björn; Unterberg, Andreas; Piek, Jürgen (Acta neurochirurgica, 2019)
BackgroundThe objective of this study was to evaluate the morphology of glioblastoma on structural pretreatment magnetic resonance imaging (MRI), defining imaging prognostic factors.MethodWe conducted a retrospective analysis of MR images from 114 patients harboring a primary glioblastoma, derived from two neurosurgical departments. Tumor segmentation was carried out in a semi-automated fashion. Tumor compartments comprised contrast-enhancing volume (CEV+), perifocal hyperintensity on fluid-attenuated inversion recovery (FLAIR) images (FLAIR+) excluding CEV+, and a non-enhancing area within the CEV+ lesion (CEV−). Additionally, two ratios were calculated from these volumes, the edema-tumor ratio (ETR) and necrosis-tumor ratio (NTR). All patients received surgical resection, followed by concomitant radiation and chemotherapy.ResultsTumor segmentation revealed the strongest correlation between the CEV+ volume and the CEV−, presenting intratumoral necrosis (p < 0.001). The relation between the tumor surrounding the FLAIR+ area and the CEV+ volume and the ETR is inversely correlated (p = 0.001). The most important prognostic factor in multivariable analysis was NTR (HR 2.63, p = 0.016). The cut-off value in our cohort for NTR was 0.33, equivalent to a decrease in survival if the necrotic core of the tumor (CEV−) accounts for more than 33% of the tumor mass itself (CEV+).ConclusionsOur data emphasizes the importance of the necrosis-tumor ratio as a biomarker in glioblastoma imaging, rather than single tumor compartment volumes. NTR can help to identify a subset of tumors with a higher resistance to therapy and a dismal prognosis.